2007
DOI: 10.2307/25549715
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a School-Based Reproductive Health Education Program in Rural South Western, Nigeria

Abstract: This quasi-experimental study compared the relative efficacy of teacher instructions alone, peer education alone, and a combination of these two on reproductive health knowledge, attitude, perceived self-efficacy and sexual practices among secondary schools students in the Ibarapa district of Southwestern Nigeria. A baseline questionnaire was administered to a systematic sample of students in four schools that were randomized into four treatment arms: teacher instructions alone (E1), peer education alone (E2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 11 publications
4
25
1
Order By: Relevance
“…Findings from other settings have suggested that including communities in the design and gaining approval from stakeholders are features of effective programs, particularly where the program covers topics that are culturally sensitive or controversial [33]. Combining school-based peer education with teacher-led programs may be more effective than teacher-led education alone [35], and was an approach suggested by some adolescents in this study. Secondary enrolment rates have been increasing in Vanuatu, however only 32% of adolescents currently attend secondary school [36].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from other settings have suggested that including communities in the design and gaining approval from stakeholders are features of effective programs, particularly where the program covers topics that are culturally sensitive or controversial [33]. Combining school-based peer education with teacher-led programs may be more effective than teacher-led education alone [35], and was an approach suggested by some adolescents in this study. Secondary enrolment rates have been increasing in Vanuatu, however only 32% of adolescents currently attend secondary school [36].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents (10-19 years) who are mostly secondary school pupils account for a significant proportion of Nigeria's population of 140 million 5. In 2001, the findings from the Statistics of the National Study of the School Health System in Nigeria carried out by the Federal Ministry of Health and Federal Ministry of Education in collaboration with the WHO revealed that health-care services in schools have not been properly implemented, thus it was noted that there was a lack of standard guiding SHP in Nigeria, which established the need for the National School Health Policy (NSHP) 6…”
Section: Introductionmentioning
confidence: 99%
“…This PSE has been applied in different surveys to gauge the extent to which young persons have the ability or confidence to adopt safer sexual behaviours including abstinence, purchase of condom, distribution of condoms, and use of condoms [35]. According to this theory, the higher a person's PSE to adopt safer sexual behaviour the higher the probability that he/she will actually put into practice such behaviour [12,35,36]. Only about half of the respondents in this study had high PSE for safe sex.…”
Section: Discussionmentioning
confidence: 99%